2023
DOI: 10.1093/nar/gkad540
|View full text |Cite
|
Sign up to set email alerts
|

ZMYM2 is essential for methylation of germline genes and active transposons in embryonic development

Abstract: ZMYM2 is a transcriptional repressor whose role in development is largely unexplored. We found that Zmym2−/− mice show embryonic lethality by E10.5. Molecular characterization of Zmym2−/− embryos revealed two distinct defects. First, they fail to undergo DNA methylation and silencing of germline gene promoters, resulting in widespread upregulation of germline genes. Second, they fail to methylate and silence the evolutionarily youngest and most active LINE element subclasses in mice. Zmym2−/− embryos show ubiq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Interestingly, we found that the more recently evolved LTRs and LINEs that retain transcription had the most highly significant gain of methylation. DNA methylation is required to maintain repression of ERV and LINE transposons in postimplantation embryos ( Dahlet et al 2020 ; Graham-Paquin et al 2023 ), suggesting that hypermethylation may interfere with their timely activation and ZGA in early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the more recently evolved LTRs and LINEs that retain transcription had the most highly significant gain of methylation. DNA methylation is required to maintain repression of ERV and LINE transposons in postimplantation embryos ( Dahlet et al 2020 ; Graham-Paquin et al 2023 ), suggesting that hypermethylation may interfere with their timely activation and ZGA in early embryos.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Similar to de novo DNMTs, a common molecular signature upon loss of PRC1.6 in embryogenesis or embryonic stem cells is the loss of promoter DNA methylation and de-repression of germline genes. [18,19,[21][22][23] Further, most components of PRC1.6 KO have been found to be necessary for embryo survival. [18,[24][25][26][27][28] Although there are varying severities observed across PRC1.6 KO models, many complex components have additional roles and/or functional redundancies that could explain some of this variability.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19,[21][22][23] Further, most components of PRC1.6 KO have been found to be necessary for embryo survival. [18,[24][25][26][27][28] Although there are varying severities observed across PRC1.6 KO models, many complex components have additional roles and/or functional redundancies that could explain some of this variability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation